Ludwig's applied process design for chemical and petrochemical plants. Volume 3 - Coker, A. Kayode (Elsevier, 2015)
The fourth edition of Ludwig's Applied Process Design for Chemical and Petrochemical Plants, Volume Three is a core reference for chemical, plant, and process engineers and provides an unrivalled reference on methods, process fundamentals, and supporting design data. New to this edition are expanded chapters on heat transfer plus additional chapters focused on the design of shell and tube heat exchangers, double pipe heat exchangers and air coolers. Heat tracer requirements for pipelines and heat loss from insulated pipelines are covered in this new edition, along with batch heating and cooking of process fluids, process integration, and industrial reactors. The book also looks at the troubleshooting of process equipment and corrosion and metallurgy.
Keywords: Chemical processes.; Chemical plants -- Equipment and supplies.; Petroleum industry and trade -- Equipment and supplies.; elektronické knihy; electronic books